2021
DOI: 10.3389/fpls.2021.710268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methyl Salicylate on Host Plant Acceptance and Feeding by the Aphid Rhopalosiphum padi

Abstract: Methyl salicylate (MeSA) is a volatile shown to act as an inducer of plant defense against pathogens and certain herbivores, particularly aphids. It has been shown to have potential for aphid pest management, but knowledge on its mode of action is lacking, particularly induced plant-mediated effects. This study investigated the effects of exposing plants to MeSA on the host searching, host acceptance and feeding behavior of the bird cherry-oat aphid Rhopalosiphum padi. Barley plants were exposed to volatile Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…However, the importance of the increased number of potential drops in plant resistance against aphids is still unknown (Sun et al 2018). Volatiles from damaged plants, such as methyl salicylate, induce effects on the leaf surface resistance factor, prolonging the time until the first probe on exposed, compared to unexposed, barley plants (Ninkovic et al 2021). The recent review paper suggested that volatile cues can induce early responses by changing the receiving plant surface (Brosset and Blande 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of the increased number of potential drops in plant resistance against aphids is still unknown (Sun et al 2018). Volatiles from damaged plants, such as methyl salicylate, induce effects on the leaf surface resistance factor, prolonging the time until the first probe on exposed, compared to unexposed, barley plants (Ninkovic et al 2021). The recent review paper suggested that volatile cues can induce early responses by changing the receiving plant surface (Brosset and Blande 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, barley exposed to deuterated methyl salicylate showed significant qualitative and quantitative changes in the chemical profile of the headspace. [51] Methyl salicylate is also known as a mobile signal to induce systemic acquired resistance against biotrophic pathogens in the tobacco plant. [52] Ethyl and methyl salicylates are the major aromatic constituents in solvent extracts of the tar tree flowers, while phenylpropanoids and phenylbutanoids are present only in minute amounts.…”
Section: Resultsmentioning
confidence: 99%
“…GC-MS results showed that the volatile compounds and the release amount reached the maximum at 24 h after treated with 1 mmol/L and 0.5 mmol/L MeSA, and decreased gradually at 48 h and 72 h. However, D-limonene and MeSA emissions dramatically increased at 72 h. This may have opened up the de novo synthesis pathway of MeSA. This pathway could be opened after wheat was treated with MeSA and the release amount of MeSA was gradually increased [31].…”
Section: Discussionmentioning
confidence: 99%